DESIGN AND IMPLEMENTATION OF NEW STUDENT ADMISSION APPLICATION AS A MARKETING MEDIUM WITH AGILE METHOD AT AL-HIKMAH KINDERGARTEN - Yohanah, Yohanah; Suryadi, Suryadi; Komara, Dewi (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
The process of accepting new students, which is still manual, can contain several obstacles such as administrative complexity, time-consuming. Therefore, through the implementation of the online system, Al-Hikmah Kindergarten hopes to accelerate and facilitate the admission of new students, provide better services to parents or guardians of students, and improve administrative management. In addition, the system can provide useful information about educational programs. Al-Hikmah Kindergarten is a must and strategic to improve the quality of educational services and meet the demands of sustainable development in an increasingly digital era. The qualitative research method is called a new method, because its popularity has not been long ago, it is called the postpositivistic method because it is based on the philosophy of postpositivism. This method is also called the artistic method, because the research process is more artistic (less patterned), and is called an interpretive method because the data from the research is more related to the interpretation of the data found in the field. Agile design method The concept of Agile Software Development was initiated by Kent Back and 16 of his colleagues stated that the concept of Agile Software Development is a way of building software by doing it and helping others and building it at the same time. From the results of this research, it can make it easier for Al-hikmah Kindergarten schools to receive the registration process and documentation process so that all processes that run can be used online and structured in the registration process. The online system can also reduce long queues, minimize the risk of loss and damage to prospective student data and speed up the data verification process. Continuous development, continue to evaluate and develop periodically to adjust to user needs and technological changes. User feedback should be integrated into every development interaction.